Excel-Based Financial Reporting for Grocery Stores in Rajabasa - Susanto, Agung; Nurmala, Nurmala; Damayanti, Damayanti (Penerbit Goodwood, 2025)
Purpose: This study aims to address the financial management challenges faced by grocery stores in Rajabasa, Bandar Lampung, due to business competition and limited financial literacy. It focuses on developing an Excel-based financial reporting application that is user-friendly for store owners without accounting backgrounds. The study also includes training and assistance to enable independent and sustainable usage. Methodology: From a population of 278 grocery stores, 74 were selected using the Slovin formula with a 10% margin of error. One store was chosen for a case study. A mixed-method approach was used, combining qualitative and quantitative techniques such as documentation, questionnaires, interviews, observation, and focus group discussions. The application features automated modules for journals, ledgers, financial statements, and inventory reports. Results: All respondents (100%) still used manual bookkeeping, citing limited technological skills, fear of errors, and difficulty in profit tracking. The Excel-based application simplified transaction recording and report generation, increased accuracy, and enhanced financial insight. Training and mentoring significantly improved users’ ability to operate the system independently. Conclusion: The study demonstrates that a simple, Excel-based financial reporting application can improve financial management in traditional grocery stores. It presents a scalable, low-cost model for enhancing financial literacy and operational efficiency among MSMEs in underserved areas. Limitations: This research was limited to a single grocery store and has not been tested on other types of MSMEs. Contributions: The study offers a practical solution for small business financial management and supports the digital literacy of MSME owners.